Research of the Real Time PCR method for detection and identification phytoplasmas on grapevine - G N Matyashova; V G Zaets (RUDN Journal of Agronomy and Animal Industries, 2015)
For the detection and identification of Candidatus Phytoplasma vitis Flavescence doree - the yellowing grape quarantine pest for the territory of Russia and Candidatus Phytoplasma solani Bois noir - pathogen of blackening crust grape was used one of the existing methods of diagnosis PCR in “real time” (RT-PCR). Matched to the fragment 16SrRNA gene species-specific primer systems were tested for false positive and false negative results for the detection of plant material in the above two phytoplasmas. According to the results of PCR in “real time”, it was determined that the studied pairs of primers allow the identification of target species phytoplasmas. Cross-reactions with other species phytoplasmas were not detected. Primers pairs do not give false positive reactions with gram-positive bacteria and some types of bacterial microflora grapes. The primer pairs and probes FDrt and BNrt can be used to detect and identify phytoplasmas - pathogens FD and BN in the regulated articles, as well as monitoring. RT-PCR method is considered to be relatively simple to implement and does not require time-consuming for the detection results.